Strategi Pengembangan Industri Bandeng Presto Bu Jumiati Di Kecamatan Juwana Kabupaten Pati - Ani Rakhmawati; Sri Marwanti; Setyowati Setyowati (Universitas Sebelas Maret, 2018)
The research aims to determine the cost, revenue, profit of industry milkfish presto Bu Jumiati, identify internal and external factors that affecting the development industry milkfish presto Bu Jumiati, to determine alternative strategy and strategy priority in development of industry milkfish presto Bu Jumiati. The basic method of research is descriptive with case study implementation technique. The location of the research is determined by purposive in industry milkfish presto Bu Jumiati. Analysis of the data used are (1) Analysis of cost, revenue, and profit, (2) IFE, (3) EFE, (4) SWOT, (5) QSPM. The results showed (1) Total cost of expenditure of Idr 69.043.750, the receipt of Idr 83,4 million, profit of Idr 14.356.250; (2) IFE indicates there are eight strengths and six weaknesses; (3) EFE shows there are five opportunities and five threats; (4) Alternative strategies that can be applied is to seek certificates of PIRT, halal certificate and include expiration date on product packaging, make improvements to bookkeeping management, design sales promotion with online media to increase sales and increase market development, foster strong motivation Owner of industry milkfish presto to attend information technology training and financial management; (5) A good strategic priority to apply is to obtain a PIRT certificate, a Halal certificate and include an expiration date on the product packaging.